Oxygen evolution catalysts at transition metal oxide photoanodes: their differing roles for solar water splitting - Zhang,J; Cui,J; Eslava,S (Advanced Energy Materials, 2021)
In the field of photoelectrochemical water splitting for hydrogen production, dedicated efforts have recently been made to improve water oxidation at photoanodes, and in particular, to accelerate the poor kinetics of the oxygen evolution reaction which is a key step in achieving a viable photocurrent density for industrialization. To this end, coating the photoanode semiconductors with oxygen evolution catalysts (OECs) has been one of the most popular options. The roles of OECs have been found to be multifold, as opposed to exclusively catalytic. This review aims to unravel the complexity of the interfacial processes arising from the material properties of both semiconductors and OECs, and to rationalize the variation in findings in the literature regarding the roles of OECs. Light is also shed on some of the most useful characterization techniques that probe the dynamics of photogenerated holes, to answer some of the field's most challenging mechanistic questions. Finally, some ideas and suggestions on the design principles of OECs are proposed.